Dyned Programme as Computer Assisted Language Learning (CALL) for University Students: A Perception and Its Impact - Prastikawati, Entika Fani (International journal of emerging technologies in learning, 2019)
This paper explores the student’s perception on the application of Dyned Programme as Computer Assisted Language Learning (CALL) in English department of Universitas PGRI Semarang, Indonesia. This study is descriptive qualitative. Otherwise, it needs the statistical data in calculating the result percentage. It took 85 students of the first semester students who have already joined Integrated Course (IC) as the sample. IC is a subject which involves ICT-based learning. In this case, Dyned Programme is the ICT-based learning used as CALL. The result of this study shows that the students are satisfied with ICT facilities provided as the media in English teaching and learning. In addition, the use of Dyned Programme in English teaching and learning is well-accepted by the students. Moreover, it comes to the students’ perception that shows us how important the media of ICT in English teaching learning process in order to make the students interest in learning English.